Meeting national land use related objectives while safeguarding typical landscapes - Valujeva, Kristine; Nipers, Aleksejs; Grinfelde, Inga; Liepa, Sindija (Landscape Architecture and Art, 2023)
Landscapes play a significant role in the regional development by providing ecosystem services to the local communities. Significant changes in land management due to the political decisions may significantly change the typical landscape in rural areas. Therefore, the aim of this study is to explore how to use the landscape differences to facilitate achievement of national socio-economic and environmental objectives, while avoiding significant changes and safeguarding typical landscapes. Cluster analysis was used to identify relatively homogeneous groups with four socio-economic and environmental indicators, namely, profit, employment, net GHG emissions, habitat quality. Results show that clusters with the highest socio-economic return are located closest to the capital city and carbon sequestration measures may be concentrated in the landscapes that are geographically farthest from the capital city, but then the abandonment of rural areas and the disappearance of typical landscapes may occur. The political decisions related to land use change should be adapted to the specific landscape, so that not only socio-economic and environmental objectives are achieved together with the fulfilment of international obligations, but also the typical landscape of the specific landscape region is preserved.